2006
DOI: 10.1002/mnfr.200600016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of quercetin and rutin by the pig caecal microflora prepared by freeze-preservation

Abstract: Several studies confirm a protection of cardiovascular diseases and certain forms of cancer by dietary flavonoid intake. The bioavailability of flavonoids is influenced by the metabolism of the microflora in the intestine. Using a new in vitro model system the deglycosylation of the flavonol rutin and the degradation of its aglycone quercetin were investigated by using fresh pig caecal inocula in comparison to inocula prepared before by freeze-preservation between 6 wk and 5 months. The incubation experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Compounds were identified by comparison of the UV spectra and the retention times. The following wavelengths were monitored for quantitative analysis: 360 nm for quercetin, 280 nm for metabolites (12, 13). …”
Section: Methodsmentioning
confidence: 99%
“…Compounds were identified by comparison of the UV spectra and the retention times. The following wavelengths were monitored for quantitative analysis: 360 nm for quercetin, 280 nm for metabolites (12, 13). …”
Section: Methodsmentioning
confidence: 99%
“…An aliquot of the filtrates was inactivated by sterilization at 121 °C for 15 min at 1.1 bar. The inactivated fecal suspensions were used as control for chemical degradation and matrix effects …”
Section: Methodsmentioning
confidence: 99%
“…In an in vitro study utilizing the flora from pig cecum, rutin was shown to by deglycosylated to quercetin and it could be further metabolized to phloroglucinol and 3,4-dihydroxyphenylacetic acid (97). The result was different when human gut microflora was used, where quercetin was metabolized to 4hydroxybenzoic acid, 3,4-dihydroxybenzoic acid, and 3,4dihydroxyphenylacetic acid (14).…”
Section: Flavonolsmentioning
confidence: 97%